Aṡāru Ta’līm Durūs al-Lugah l-‘Arabiyyah ‘alā Kafāati Mahārah al-Kalām Liţholabah Ma’had al-Risālah al-‘Aṣrī al-Mubarmaj al-‘Ālamī Biponorogo - Tiara Mustika Hanum Mar'ati; Wahyu Hanafi Putra; Kunti Nadiyah Salma (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
Abstract The teachings of Durūs al-Lughah al-'Arabiyah are found in many Modern Universities as a teaching foundation for developing the four language skills. Students need this teaching to know about Arabic. This study aims to determine: (1) The condition of speaking skills in the first grade before learning Durusul lughah al-'Arabiyah, (2) The Teaching System of Durūs al-Lughah al-'Arabiyah in class, (3) The effect of teaching Durūs al-Lughah al-'Arabiyah 'Arabiyah on speaking skills and the results of the correlation between the two. The approach used in this research is quantitative. The population is 49 students of the first-grade students of the Ar Risalah Ponorogo Islamic Boarding School, while the sample is taken using random sampling. Data collection techniques uses observation, questionnaires, and documentation. The data analysis uses Product Moment Correlation. The results of the study are: 1) Before the students learn Durusul Lughah, many do not know or understand Arabic and how to give answers when they are questioned about things in Arabic. 2) Learning Durusul Lughah in this pondok uses the behavioral method where students are required to memorize vocabulary and use Arabic with simple vocabulary. 3) Based on the product-moment correlation calculations, it was found that there was a relationship between the teaching of Durusul Lughah and its efficiency towards the speaking skill of the first grade students of the Ar Risalah Ponorogo Islamic Boarding School. The correlation value was 0.718 which means H0 is rejected and Ha is accepted. In other words,  there is a relationship between Durusul Lughah learning and speaking skills of female students of class 1 at Ar Risalah Islamic Boarding School Ponorogo. Keyword : Teaching; speaking; correlation